2006
DOI: 10.2981/0909-6396(2006)12[211:visiro]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Variation in stable isotope ratios of carbon and nitrogen in Hokkaido sika deer Cervus nippon during 1990–2000: possible causes and implications for management

Abstract: Sika deer Cervus nippon populations in eastern Hokkaido, Japan, increased rapidly during 1990-1998. This increase appeared to have halted in 1999-2000, probably due to increased hunting and nuisance control. The period of rapid increase was associated with a disproportionately rapid increase in compensation paid for deer damage to crops. We studied changes in diet during 1990-2000, as reflected by stable isotope ratios of C and N in tooth collagen. We hypothesised that isotope ratios would demonstrate dietary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 18 publications
(21 reference statements)
0
8
0
Order By: Relevance
“…Carbon and nitrogen isotope signatures of bone and antler are now often used to reconstruct the ecological conditions in which ancient deer lived, to track past habitat changes in the vicinity of the sites of recovery, and to infer past human management practices . They are also used to define isotopic baselines with which human isotope signatures can be compared .…”
Section: Bone and Antler Structure And Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Carbon and nitrogen isotope signatures of bone and antler are now often used to reconstruct the ecological conditions in which ancient deer lived, to track past habitat changes in the vicinity of the sites of recovery, and to infer past human management practices . They are also used to define isotopic baselines with which human isotope signatures can be compared .…”
Section: Bone and Antler Structure And Compositionmentioning
confidence: 99%
“…Carbon and nitrogen isotope signatures of bone and antler are now often used to reconstruct the ecological conditions in which ancient deer lived, to track past habitat changes in the vicinity of the sites of recovery, and to infer past human management practices. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] They are also used to define isotopic baselines with which human isotope signatures can be compared. [20,21] This is possible as herbivore proteinaceous body tissues predominantly reflect the isotopic composition of the plants (primarily that of the protein) consumed by the herbivore, potentially modulated by physiology and diet composition, [22][23][24][25][26][27][28][29][30][31] and there is isotopic variation in plants within and between ecosystems in both space and time due to physiological and environmental/climatic parameters.…”
mentioning
confidence: 99%
“…The leaves of the 2 bamboo species measured in this study had more negative δ 13 C values than the average for C3 plants as they are growing under a canopy. The results show similar δ 13 C and δ 15 N to the leaves of a dwarf bamboo (Halley et al 2006) and 2 herbaceous bamboo species (Pharus latifolius Linnaeus, 1759 and Streptochaeta sodiroana Hack, 1890) growing under the sun in growing house conditions (Silveira et al 1989).…”
Section: Characteristics Of Bamboo Discrimination Factorsmentioning
confidence: 68%
“…Quantitative analyses of feces of Hokkaido sika deer have shown that the deer were dependent on dwarf bamboo (Table 1), which had δ 13 C of −30.8 ± 0.40‰, being a significantly more negative value than that of other plants in the same habitat (− 29.7 ± 1.20‰) (Halley et al, 2006). This reflects a more prominent canopy effect on dwarf bamboo because it grows near the ground, covering the forest floor.…”
Section: Comparisons Of Stable Isotopic Values Of Fossil Deer With Exmentioning
confidence: 96%